Limited Retreat of the Wilkes Basin Ice Sheet During the Last Interglacial. Issue 13 (25th June 2020) - Sutter, J.; Eisen, O.; Werner, M.; Grosfeld, K.; Kleiner, T.; Fischer, H.
Abstract: The response of the East Antarctic Ice Sheet to global warming represents a major source of uncertainty in sea‐level projections. Thinning of the East Antarctic George V and Sabrina Coast ice cover is currently taking place, and regional ice‐sheet instability episodes might have been triggered in past warm climates. However, the magnitude of ice retreat in the past cannot yet be quantitatively derived from paleo‐proxy records alone. We propose that a runaway retreat of the George V coast grounding line and subsequent instability of the Wilkes Basin ice sheet would either leave a clear imprint on the water isotope composition in the Talos Dome region or prohibit a Talos Dome ice‐core record from the Last Interglacial altogether. Testing this hypothesis, our ice‐sheet model simulations suggest that Wilkes Basin ice‐sheet retreat remained relatively limited during the Last Interglacial and provide a constraint on Last Interglacial East Antarctic grounding line stability. Plain Language Summary: The Wilkes Basin ice sheet, located in East Antarctica, harbors enough ice to raise global sea level by several meters. Just like the West Antarctic Ice Sheet, it is vulnerable to ocean warming and is currently losing mass at an accelerated pace. The Last Interglacial ca. 130, 000 years ago witnessed global temperatures that are probably surpassed during the next decades and serves as a potential analog for a future warmer planet. We show that during this time, one of the largest marine sectors of the East Antarctic Ice Sheet only contributed relatively little to global sea‐level rise. This indicates that keeping global temperatures in check could safeguard at least parts of the Antarctic Ice Sheet from irreversible mass loss. Key Points: A marine ice sheet instability in the Wilkes Basin would substantially accelerate ice flow in the Talos Dome region The Talos Dome ice core record shows no sign of dynamic thinning during the Last Interglacial The Wilkes Basin probably remained relatively stable during the Last Interglacial; thus, the majority of ice loss originated from WAIS